Study on Precision during Articulator Handling - Sawada, Shoji (Nihon Hotetsu Shika Gakkai Zasshi, 1989)
Using several brands of articulators, the precision involved in the manipulation of them was examined. First of all, the extent of three-dimensional displacement caused in the upper frame was examined when the ‘Inclination of sagittal condyle path’(I. S. C. P.) and the ‘Inclination of sagittal incisal path’(I. S. I. P.) of articulators were adjusted. Secondly, the displacement was measured, which is caused as it was loaded statically to the center of the upper frame. Thirdly, the vertical displacement of the upper frame and cast were measured when the cast is mounted by the plaster. Following results were obtained. The various displacement occurred between the upper and lower frame during articulator handling. After all, the rigidity or the precision of articulators should be taken into consideration, and the I. S. C. P. should be adjusted to 30° and the I. S. I. P. to 0° as the upper cast was mounted. However, the error due to three-dimensional displacement was found, which was caused by these adjustments after mounting casts. When casts are mounted with high or low ratio of water and powder, the expansion was smaller in the case of high ratio, so the ratio should be taken into consideration. Accordingly, I planned out the ‘Remounting Method’ which is able to use the articulator in high precision.